2015
DOI: 10.1021/ed500793q
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Integrated Laboratory and Inquiry-Based Research Experience: Replacing Traditional Laboratory Instruction with a Sustainable Student-Led Research Project

Abstract: has replaced its junior-and senior-level laboratory curriculum with two, two-semester long, student-led research projects as part of the department's American Chemical Society-accredited program. In the first semester of each sequence, a faculty instructor leads the students through a set of previously performed experiments and introduces the students to a research project, specific laboratory techniques, and instrumentation. As such, the first (fall) semester takes the form of a control experiment. During the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 26 publications
(42 reference statements)
0
30
0
Order By: Relevance
“…In particular, the students were satisfied with the h-PBL format because they considered that this method helped them learn relatively complex and nonintuitive parts of the program more easily than with pure PBL. They also noted the cooperative work and informational skills (Carrio et al, 2016) and the ability of thinking indendently and critically (Hartings et al, 2015) as reinforcements of the acquired skills in h-PBL. In the study by Yang et al, (Yang et al, 2014) the questionnaire conducted on the h-PBL and TT groups, showed that some students had negative feedback on pure PBL, which was mainly due to the difficulties had by the students to gain a comprehensive understanding of the subjects.…”
Section: Students Perceptionmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, the students were satisfied with the h-PBL format because they considered that this method helped them learn relatively complex and nonintuitive parts of the program more easily than with pure PBL. They also noted the cooperative work and informational skills (Carrio et al, 2016) and the ability of thinking indendently and critically (Hartings et al, 2015) as reinforcements of the acquired skills in h-PBL. In the study by Yang et al, (Yang et al, 2014) the questionnaire conducted on the h-PBL and TT groups, showed that some students had negative feedback on pure PBL, which was mainly due to the difficulties had by the students to gain a comprehensive understanding of the subjects.…”
Section: Students Perceptionmentioning
confidence: 97%
“…In addition, students had the opportunity to comment on the contents of the tutorial, as well as express their opinions and suggestions to improve the course (Carrio et al, 2016;Hartings et al, 2015;Lian & He, 2013;Yang et al, 2014).…”
Section: Students Perceptionmentioning
confidence: 99%
“…PBL is a pedagogical approach in which students actively participate in the investigation of real-world problems and in the process gain experience in asking questions, predicting results, designing and carrying out experiments, analyzing data, and communicating results to others [1]. In the undergraduate chemistry context, PBL often takes the form of student-designed research projects of varying scope and complexity [2][3][4][5][6][7][8][9]. PBL and other active learning approaches can sometimes be met with student resistance [10], and student feedback collected as part of some of the PBL initiativescited above indicated that students were often challenged-and in some cases frustrated-by the process, despite also finding it rewarding [3,9].…”
Section: Chem 305 and Project-based Learningmentioning
confidence: 99%
“…PBL and other active learning approaches can sometimes be met with student resistance [10], and student feedback collected as part of some of the PBL initiativescited above indicated that students were often challenged-and in some cases frustrated-by the process, despite also finding it rewarding [3,9]. However, student responses also highlighted a wide range of benefits of PBL, including increased confidence in the laboratory and with research in general [2,4,5], improved experimental design skills [4], and development of critical thinking skills [5,9]. In addition, students reported that they enjoyed the freedom to plan their own experiments and take ownership over their own projects [2,3,8].…”
Section: Chem 305 and Project-based Learningmentioning
confidence: 99%
“…Online learning is an effective modality for delivering continued and professional education to working professionals, especially when offered with interactive delivery methods, discussion boards, and multiple audio/ visual resources (12)(13)(14)(15)(16). New paradigms of teaching and course development that engage the learner, integrate different disciplines into core content, and cover professional competencies are emerging that offer crosscutting experiences to promote sustainability and health at all levels: individual, population, and global (17)(18)(19)(20)(21)5). The Molecular Design Research Network (MoDRN) has developed educational tools and strategies for students, educators, the scientific community, and practitioners to explore safer chemical design (22).…”
Section: Introductionmentioning
confidence: 99%